Ekonomi Syariah di Persimpangan Jalan: Lompatan Strategis Indonesia dari Kebijakan ke Dampak - Mohammad Muafi Himam; Rendy Dwi Hermanto; Adam Permadi Kaharudin; Ahmad Maimun (Institut Agama Islam (IAI) SEBI, 2025)
This article evaluates Indonesia's Islamic economic policies during the 2019–2024 period across four key sectors: Islamic banking, halal industry, sukuk and Islamic financing, and Islamic fintech. Adopting an explanatory sequential mixed-methods design, the study integrates descriptive quantitative analysis of secondary data from OJK, KNEKS, BPJPH, DJPPR, BPS, and the SGIE Report 2024/2025 with qualitative content analysis of policy documents, including MEKSI 2019–2024, RP3SI 2023–2027, POJK 2/2024 on Sharia Governance, and the Republic of Indonesia Green Bond and Green Sukuk Framework. The findings indicate that government interventions—including the merger forming Bank Syariah Indonesia, the issuance of green sukuk reaching a cumulative USD 7.7 billion through 2025, the digitalisation of halal certification via SiHalal, and the institutionalisation of KNEKS and 31 provincial KDEKS—are associated with measurable improvements: Indonesia's third place in the Global Islamic Economy Indicator, total Islamic financial assets of IDR 2,756.45 trillion as of June 2024, and rising Islamic financial literacy from 9.14% in 2022 to 43.42% in 2025. However, persistent challenges remain, namely a banking market share stuck at 7.72%, halal exports concentrated in non-OIC markets, and weak fintech governance. The study is limited to secondary data and does not include expert interviews. Future research should incorporate in-depth interviews and micro-level welfare assessments to strengthen causal interpretation. Artikel ini mengevaluasi kebijakan ekonomi syariah Indonesia selama periode 2019–2024 pada empat sektor utama: perbankan syariah, industri halal, sukuk dan pembiayaan syariah, serta fintech syariah. Penelitian menggunakan desain explanatory sequential mixed-methods yang memadukan analisis deskriptif kuantitatif atas data sekunder OJK, KNEKS, BPJPH, DJPPR, BPS, dan laporan SGIE 2024/2025 dengan analisis konten dokumen kebijakan, antara lain MEKSI 2019–2024, RP3SI 2023–2027, POJK 2/2024 tentang Tata Kelola Syariah, dan Republic of Indonesia Green Bond and Green Sukuk Framework. Temuan menunjukkan bahwa intervensi pemerintah—mencakup merger pembentukan Bank Syariah Indonesia, penerbitan green sukuk dengan akumulasi USD 7,7 miliar hingga 2025, digitalisasi sertifikasi halal melalui SiHalal, dan pelembagaan KNEKS bersama 31 KDEKS provinsi—berasosiasi dengan perbaikan indikator yang dapat diukur, antara lain peringkat ketiga Indonesia dalam Global Islamic Economy Indicator, total aset keuangan syariah Rp2.756,45 triliun per Juni 2024, dan kenaikan literasi keuangan syariah dari 9,14% pada 2022 menjadi 43,42% pada 2025. Akan tetapi, tantangan struktural masih membayangi: pangsa pasar perbankan syariah bertahan di 7,72%, ekspor halal masih terkonsentrasi pada pasar non-OKI, dan tata kelola fintech syariah belum kuat. Penelitian ini terbatas pada data sekunder dan tidak menyertakan wawancara pakar. Penelitian lanjutan disarankan menambahkan wawancara mendalam dan kajian kesejahteraan tingkat mikro untuk memperkuat interpretasi kausal.